Readership of AG Outlook Inserts in Farm Magazines - Jack Sperbeck (Journal of Applied Communications, 1982)
In late September 1981, we surveyed Minnesota subscribers to The Farmer magazine to see how well they read an editorial insert called "1981 Ag Outlook."